Slope Stability At Km 50.0, Teluk Bahang, Pulau Pinang Using Resistivity Method - Bujang, Mohamad Nizamhadi (Universiti Sains Malaysia, 2006)
Landslides and related slope instability phenomena affects many parts of the world including Malaysia. For many years, landslide is a common occurrence in Malaysia. As a result of this disastrous phenomenon, large number of death and economic losses were reported. This study focuses on the electrical resistivity distribution on a cut slope located at Km 50.0, Teluk Bahang, Pulau Pinang. Generally, the study area is overlyaid by thick profile of highly weathered to residual soil of granitic, resulting from intense in-situ weathering of Feringghi Granite. A 2-D Resistivity Imaging is used in mapping the electrical resistivity distribution at the study area. Electrical resistivity imaging can help in identifying the presence of water and other geological features underneath the ground. Three survey lines were established perpendicular to the cut slope (berm) for data acquisition purposes. Result shows that the presence of core boulders, weak zones, fractured zones and cracks detected on the study area. Besides this, a landslide is predicted to happen in one of the survey lines based on its resistivity features. This implies that the 2-D Resistivity Imaging method is an effective technique for slope stability investigation.